Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Beyond size and shape: Physicochemical properties of microplastic test materials generated by cryomilling - Lucy Howarth-Forster; Robyn Barrett; Robert Clough; Lisbet Sørensen; Jack Allen; Chris Powell; Richard C. Thompson; Matthew Cole; Michael Wilde (Journal of Hazardous Materials, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Earthquake-triggered submarine canyon flushing transfers young terrestrial and marine organic carbon into the deep sea - Katherine L Maier; Catherine E Ginnane; Sebastian Naeher; Jocelyn C Turnbull; Scott D Nodder; Jamie Howarth; Sarah J Bury; Robert G Hilton; Jess IT Hillman (Earth and Planetary Science Letters, 2025)

Place-based climate commissions: embracing messy governmentality - C. Howarth; L. Edwards; A. Duncan; D. Van der Horst; R. Pringle (Climatic Change, 2024)
The role of the ‘place’ in delivering climate action is vital, however much action on climate change locally is fragmented. Independent place-based climate commissions are a novel structure of climate governance developing at the subnational level across cities, regions and counties in the UK. Little is known about these emerging forms of local climate governance and their experiences of navigating ‘mess’ in governance practices and processes. Building on Castán Broto’s framework of messy governmentalities, this paper seeks to assess the capacity of climate commissions to affect meaningful climate mitigation and adaptation action, to understand how they interact with existing climate governance structures and to consider their longer-term sustainability. This paper examines the nature and impact climate commissions have had on local climate action, drawing on qualitative interviews with chairs, commissioners, members of the secretariat and associated local authorities of the Edinburgh, Belfast, Leeds, Surrey, Yorkshire and Humber, and Lincoln commissions in the UK. Analysing the journeys of the commissions through a lens of messy governmentalities, and a focus on bodies, strategies and knowledges within them, we draw out insights on how climate commissions came about, their function and role, their impact and influence, and how they have evolved.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The capturing and decompression of melt inclusions in olivine and ilmenite megacrysts from the Monastery kimberlite, South Africa - S.H. Büttner; A. van Huyssteen; E. Marima; A. du Plessis; M. Tshibalanganda; C. Schmidt; G.H. Howarth (Gondwana Research, 2023)

Rapid characterisation of Mars' mantle reservoirs by in situ laser ablation 87Sr/86Sr analysis of shocked feldspar (maskelynite) - Daniel L. Burgin; James M. Scott; Petrus J. le Roux; Geoffrey Howarth; Marshall C. Palmer; Thomas A. Czertowicz; Marianne Negrini; Malcolm R. Reid; Claudine H. Stirling (Geochimica et Cosmochimica Acta, 2023)

Evidence of intrapopulation differences in rattlesnake defensive behavior across neighboring habitats - Marcus C. P. Atkins; Chloe R. Howarth; Michael A. Russello; Jabed H. Tomal; Karl W. Larsen (Behavioral Ecology and Sociobiology, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Population genomics of Mediterranean oat (A. sativa) reveals high genetic diversity and three loci for heading date - F. J. Canales; G. Montilla-Bascón; W. A. Bekele; C. J. Howarth; T. Langdon; N. Rispail; N. A. Tinker; E. Prats (Theoretical and Applied Genetics, 2021)
Key message Genomic analysis of Mediterranean oats reveals high genetic diversity and three loci for adaptation to this environment. This information together with phenotyping and passport data, gathered in an interactive map, will be a vital resource for oat genetic improvement. Abstract During the twentieth century, oat landraces have increasingly been replaced by modern cultivars, resulting in loss of genetic diversity. However, landraces have considerable potential to improve disease and abiotic stress tolerance and may outperform cultivars under low input systems. In this work, we assembled a panel of 669 oat landraces from Mediterranean rim and 40 cultivated oat varieties and performed the first large-scale population genetic analysis of both red and white oat types of Mediterranean origin. We created a public database associated with an interactive map to visualize information for each accession. The oat collection was genotyped with 17,288 single-nucleotide polymorphism (SNP) loci to evaluate population structure and linkage disequilibrium (LD); to perform a genome-wide association study (GWAs) for heading date, a key character closely correlated with performance in this drought-prone area. Population genetic analysis using both structure and PCA distinguished two main groups composed of the red and white oats, respectively. The white oat group was further divided into two subgroups. LD decay was slower within white lines in linkage groups Mrg01, 02, 04, 12, 13, 15, 23, 33, whereas it was slower within red lines in Mrg03, 05, 06, 11, 21, 24, and 28. Association analysis showed several significant markers associated with heading date on linkage group Mrg13 in white oats and on Mrg01 and Mrg08 in red oats.

Marine Conservation Begins at Home: How a Local Community and Protection of a Small Bay Sent Waves of Change Around the UK and Beyond - Bryce D. Stewart; Leigh M. Howarth; Howard Wood; Kerri Whiteside; William Carney; Éilís Crimmins; Bethan C. O’Leary; Julie P. Hawkins; Callum M. Roberts (Frontiers in Marine Science, 2020)

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

Type 1 diabetes mellitus induces structural changes and molecular remodelling in the rat kidney - Raphael M. Singh; Frank C. Howarth; Ernest Adeghate; Keshore Bidasee; Jaipaul Singh; Tehreem Waqar (Molecular and Cellular Biochemistry, 2018)

Mapping of easy to screen SSR markers for selection of RFLP markers-bracketed downy mildew resistance QTLs in pearl millet - Jyoti Taunk; Deepmala Sehgal; Neelam R. Yadav; Catherine Howarth; Ram C. Yadav; Rattan S. Yadav (European Journal of Plant Pathology, 2018)

Dapagliflozin reduces the amplitude of shortening and Ca2+ transient in ventricular myocytes from streptozotocin-induced diabetic rats - N. N. Hamouda; V. Sydorenko; M. A. Qureshi; J. M. Alkaabi; M. Oz; F. C. Howarth (Molecular and Cellular Biochemistry, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genetic Diversity and Population Structure Among Oat Cultivars and Landraces - G. Montilla-Bascón; J. Sánchez-Martín; N. Rispail; D. Rubiales; L. Mur; T. Langdon; I. Griffiths; C. Howarth; E. Prats (Plant Molecular Biology Reporter, 2013)

Effects of exercise training on excitation–contraction coupling and related mRNA expression in hearts of Goto-Kakizaki type 2 diabetic rats - K. A. Salem; M. A. Qureshi; V. Sydorenko; K. Parekh; P. Jayaprakash; T. Iqbal; J. Singh; M. Oz; T. E. Adrian; F. C. Howarth (Molecular and Cellular Biochemistry, 2013)

Contractility of ventricular myocytes is well preserved despite altered mechanisms of Ca2+ transport and a changing pattern of mRNA in aged type 2 Zucker diabetic fatty rat heart - F. C. Howarth; M. A. Qureshi; Z. Hassan; D. Isaev; K. Parekh; A. John; M. Oz; H. Raza; E. Adeghate; T. E. Adrian (Molecular and Cellular Biochemistry, 2012)

Pathogenesis and pathophysiology of accelerated atherosclerosis in the diabetic heart - Alicia D’Souza; Munir Hussain; Frank C. Howarth; Niall M. Woods; Keshore Bidasee; Jaipaul Singh (Molecular and Cellular Biochemistry, 2009)

Altered gene expression may underlie prolonged duration of the QT interval and ventricular action potential in streptozotocin-induced diabetic rat heart - F. C. Howarth; M. Jacobson; M. A. Qureshi; M. Shafiullah; R. S. Hameed; E. Zilahi; A. Al Haj; N. Nowotny; E. Adeghate (Molecular and Cellular Biochemistry, 2009)

Effects of streptozotocin-induced diabetes on connexin43 mRNA and protein expression in ventricular muscle - F. C. Howarth; N. J. Chandler; S. Kharche; J. O. Tellez; I. D. Greener; T. T. Yamanushi; R. Billeter; M. R. Boyett; H. Zhang; H. Dobrzynski (Molecular and Cellular Biochemistry, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

Altered expression of gap junction connexin proteins may partly underlie heart rhythm disturbances in the streptozotocin-induced diabetic rat heart - F. C. Howarth; N. Nowotny; E. Zilahi; M. A. El Haj; M. Lei (Molecular and Cellular Biochemistry, 2007)

Effects of streptozotocin-induced diabetes on action potentials in the sinoatrial node compared with other regions of the rat heart - F. C. Howarth; R. Al-Sharhan; A. Al-Hammadi; M. A. Qureshi (Molecular and Cellular Biochemistry, 2007)

Reconciling Carbon-cycle Concepts, Terminology, and Methods - F. S. Chapin; G. M. Woodwell; J. T. Randerson; E. B. Rastetter; G. M. Lovett; D. D. Baldocchi; D. A. Clark; M. E. Harmon; D. S. Schimel; R. Valentini; C. Wirth; J. D. Aber; et al. (Ecosystems, 2006)

Effects of carbenoxolone on heart rhythm, contractility and intracellular calcium in streptozotocin-induced diabetic rat - F. C. Howarth; M. A. Qureshi (Molecular and Cellular Biochemistry, 2006)

The progressive effects of a fat enriched diet on ventricular myocyte contraction and intracellular Ca2+ in the C57BL/6J mouse - F. C. Howarth; M. A. Qureshi; A. J. Gbewonyo; S. Tariq; E. Adeghate (Molecular and Cellular Biochemistry, 2005)

Effects of single high-dose and multiple low-dose streptozotocin on contraction and intracellular Ca2+ in ventricular myocytes from diabetes resistant and susceptible rats - F. C. Howarth; A. Qureshi; A. Shahin; M. L. Lukic (Molecular and Cellular Biochemistry, 2005)

The serine acetyltransferase gene family in Arabidopsis thaliana and the regulation of its expression by cadmium - Jonathan R. Howarth; José R. Domínguez-Solís; Gloria Gutiérrez-Alcalá; John L. Wray; Luis C. Romero; Cecilia Gotor (Plant Molecular Biology, 2003)

Quantitative trait loci associated with traits determining grain and stover yield in pearl millet under terminal drought-stress conditions - R. S. Yadav; C. T. Hash; F. R. Bidinger; G. P. Cavan; C. J. Howarth (Theoretical and Applied Genetics, 2002)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Rapid effects of cytochalasin-D on contraction and intracellular calcium in single rat ventricular myocytes - F. C. Howarth; M. R. Boyett; E. White (Pflügers Archiv - European Journal of Physiology, 1998)

Internal free magnesium modulates the voltage dependence of contraction and Ca transient in rabbit ventricular myocytes - F. C. Howarth; Allan J. Levi (Pflügers Archiv - European Journal of Physiology, 1998)

”Voltage-activated Ca release" in rabbit, rat and guinea-pig cardiac myocytes, and modulation by internal cAMP - Ion A. Hobai; F. Chris Howarth; Vijay K. Pabbathi; Geoff R. Dalton; Jules C. Hancox; Jie-Quan Zhu; Susan E. Howlett; Gregory R. Ferrier; A. J. Levi (Pflügers Archiv - European Journal of Physiology, 1997)

Dietary and physiological studies to investigate the relationship between calcium and magnesium signalling in the mammalian myocardium - Jaipaul Singh; Brenda I. Hustler; John J. Waring; Frank C. Howarth (Molecular and Cellular Biochemistry, 1997)